Comparison of the effectiveness of treatment with hyaluronic acid formulation and Ovarium compositum in women with dystrophies of the vulva - Markowska, Janina; Mądry, Radosław (Menopause Review/Przegląd Menopauzalny, 2009)
The aim of the study was to compare treatment effectiveness of vulvar dystrophy in three groups of women treated with Cicatridina, Ovarium compositum, and both drugs used simultaneously. Material and methods: In our study we included 42 women aged 26-85 with average age of 62, in whom vulvar dystrophy was diagnosed. Cicatridina cream was applied locally on the dysplastic vulvar cells, and Ovarium compositum was administered as intramuscular injections. Results and conclusions: Cicatridina is an effective drug in the therapy of local vulvar dystrophy; in 92.8% of studied women a positive response was achieved. After homeopathic treatment with Ovarium compositum a positive response is achieved in 85.7% of women with dystrophies of the vulva.